STRATEGI PENINGKATAN KUNJUNGAN WISATAWAN MELALUI OPTIMALISASI POTENSI DAN PROMOSI WISATA EFEKTIF DI PULAU MARINGKIK - Cahyowati, RR.; Faisal, Sultanfat; Yunistia, Baiq Anggi; Dewi, Ni Putu Sinta; Krisnawan, Putu Anugrah; Fujiana, Nita; Wigati, Kalis Hayu; Hamid, Moh. Gilang fawwaz; Priyono, Cinndy Ezra Paramitha; Rahayu, Bq. Intan Zulia Febi (Universitas Mataram, 2024)
Maringkik Island is part of Teluk Jukung which has abundant marine resources ranging from diverse marine flora and fauna. The purpose of this paper, is to introduce tourist attractions, improve the community’s economy, and increase visitor attractiveness in Maringkik Island Village. Research Methods, this activity is carried out through three stages, namely: promotion preparation, survey of potential tourism objects for promotion, making facilities and infrastructure, community assistance for tourism business development. Conclusion, the implementation of a comprehensive and coordinated strategy to increase tourist visits to Maringkik Island, optimizing the tourism potential in Maringkik Island Village, starting from the development of adequate infrastructure, quality improvement and local culture are important factors in attracting tourists, the involvement of local communities in the management and preservation of culture can also enrich the tourist experience and add value to this destination. Effective promotion is carried out with the use of technology and effective promotion is carried out with the use of technology, effective promotion with the use of digital technology, such as social media, websites, online tourism platforms, is crucial to reach a wider market, cooperation with government, travel agents, and the media to expand the reach of promotion, the right strategy and sustainability are the keys to Maringkik Island Village as a popular and competitive tourist destination.